An in-home rehabilitation program for the treatment of urinary incontinence symptoms in endometrial cancer survivors: a single-case experimental design study - Bernard, Stéphanie; McLean, Linda; Boucher, Samantha; Hébert, Luc J.; Plante, Marie; Grégoire, Jean; Sebastianelli, Alexandra; Renaud, Marie-Claude; Froment, Marie-Anne; Moffet, Hélène (International Urogynecology Journal, 2021)
Introduction and hypothesis There is a high prevalence of urinary incontinence among endometrial cancer survivors. They are also known to present with pelvic floor muscle alterations. Evidence on the effects of conservative interventions for the management of UI is scarce. This study aims at verifying the effects of an in-home rehabilitation program, including the use of a mobile technology, to reduce UI severity in endometrial cancer survivors. Methods This study used a single-case experimental design with replications. Primary outcome for UI severity was the pad test, and secondary outcomes were the ICIQ-UI SF questionnaire and 3-day bladder diary. Pelvic floor muscle function was assessed using 2D-transperineal ultrasound and intravaginal dynamometry. Adherence was documented using mobile technology and an exercise log. Visual and non-parametric analyses of longitudinal data were conducted. Results Results show a reduction in UI severity for 87.5% of participants, with a significant relative treatment effect of moderate size (RTE: 0.30). Significant small relative treatment effects were found for the quick contraction and endurance dynamometric tests. Conclusion This study provides new evidence that endometrial cancer survivors can improve the severity of their UI following an in-home rehabilitation program, including the use of a mobile technology. This mode of delivery has the potential to address a gap in access to pelvic floor physiotherapy services for survivors of EC living in rural and remote communities.